2015
DOI: 10.1016/j.clgc.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxidative Stress Biomarkers and Carboxymethyllysine (an Advanced Glycation End Product) on Prostate Cancer: A Prospective Study

Abstract: Introduction Biomarkers of oxidative stress and advanced glycation end products (AGE) have been linked to the development of prostate cancer, but evidence from human studies is either scarce or controversial. Materials and Methods We conducted a prospective nested case-control study among 48 men (24 prostate cancer cases and 24 controls) aged 48–76 years at baseline. The participants of our study were a part of the Fernald Community Cohort (FCC). Prostate cancer cases and controls were matched individually o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Therefore, the reports in the literature about oxidative stress biomarkers and BC risk remain controversial and more large studies are needed. In line with our finding for d‐ROM and PrC, it was previously shown that neither 8‐isoprostane levels nor FlOP were statistically significantly associated with PrC incidence in the main analyses using the total cohort's populations …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the reports in the literature about oxidative stress biomarkers and BC risk remain controversial and more large studies are needed. In line with our finding for d‐ROM and PrC, it was previously shown that neither 8‐isoprostane levels nor FlOP were statistically significantly associated with PrC incidence in the main analyses using the total cohort's populations …”
Section: Discussionsupporting
confidence: 92%
“…In line with our finding for d-ROM and PrC, it was previously shown that neither 8-isoprostane levels nor FlOP were statistically significantly associated with PrC incidence in the main analyses using the total cohort's populations. 23,31 As aforementioned, the d-ROM test assesses the total organic hydroperoxides concentration in fluids. Hydroperoxides are a battery of biomolecules generated by the oxidation of mainly lipids but also proteins and nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, in the last few years, the potential implication of AGEs in carcinogenesis has drawn the attention of investigators, and the presence of AGEs has already been described in several types of cancer [161][162][163]. Moreover, it has been found that the circulating levels of AGEs were increased in patients with prostate cancer when compared with healthy patients, with the highest levels of AGEs corresponding with high-grade prostate cancer patients, according to the Gleason score [162,164,165].…”
Section: The Increasing Relevance Of Ages In Age-associated Diseasesmentioning
confidence: 99%
“…Systematic reviews indicate that a high-AGE diet that often recognized as a Western-style diet containing high-fat/high-sugar foods, refined grains, and red meat [25] or an unhealthy/sedentary lifestyle may increase the body's AGE pool, thereby increasing the risk of cancers such as prostate and pancreatic cancer [25][26][27][42][43][44]. In addition, a series of epidemiological studies have elucidated the association of biological AGE levels with the risk of cancer in smokers [45][46][47][48] and cancer patients [49][50][51]. Studies in Finnish male smokers found that serum CML levels were not associated with the risk of pancreatic or colorectal cancer and were inversely associated with the risk of liver cancer [45][46][47].…”
Section: Epidemiological and Animal Studymentioning
confidence: 99%